D-graphs II: Constructions of D-graphs for some families of graphs with even cycles - Farrell E.J.; Wahid S.A. (Utilitas Mathematica, 1999)
The fundamental edge algorithm is extended to multigraphs. Comatching D-graphs are then found for cycles, complete graphs and complete bipartite graphs. They all turn out to be proper multi-D-graphs. However it is shown that not all graphs have a comatching proper multi-D-graph.